Dental Students' Awareness After Clinical Training Between Dental Treatment and Systemic Health: A Questionnaire-Based Survey - Naruishi, Koji; Wada-Mihara, Chie; Oishi, Keiji; Nagata, Toshihiko (Frontiers in Dental Medicine, 2022)
Clinical training is an essential program for dental students to learn clinical skills. The aim of this study was to survey whether dental students who had undergone clinical training understood the clinical significance of dental treatment and its connection to systemic health. An awareness survey was conducted in dentistry students both before and after undergraduate clinical training. A total of 42 dental students were recruited before clinical training, and 32 dental students responded to the survey. In addition, all of the 42 dental students responded to the survey after clinical training. A total of 53 medical students were recruited as control subjects. Differences between the 2 groups were analyzed using Fisher's exact test. Before clinical training, a higher percentage of dental students felt the positive effects of periodontal treatment on systemic health. A higher percentage of dental students also recognized the positive effects of prosthetic treatment on geriatric conditions. After clinical training, no significant differences were found between periodontal and prosthetic treatment when surveyed about the positive effects of dental treatment on geriatric conditions. Undergraduate clinical training is essential for improving the students’ understanding of the clinical significance of dental treatment. These surveys suggest that dental education supported by clinical experience contributes to understand the role of dental treatment.